Convergence of a proximal point algorithm for maximal monotone operators in Hilbert spaces - Wei, Zhiqiang; Shi, Guohong (Journal of inequalities and applications, 2012)
In this article, we consider the proximal point algorithm for the problem of approximating zeros of maximal monotone mappings. Strong convergence theorems for zero points of maximal monotone mappings are established in the framework of Hilbert spaces. 2000 AMS Subject Classification: 47H05; 47H09; 47J25.